Is internal migration a way to cope with weather extremes? Evidence from Egypt - Mohamed Arouri; Adel Ben-Youssef; Cuong Viet Nguyen (Journal of Economics and Development, 2023)
Purpose – In this study, the authors examine the push and pull effects of extreme weather events on migration among governorates in Egypt. Design/methodology/approach – To estimate the effect of extreme weather events on internal migration, the authors use migration gravity models and data from the 1996 and 2006 Population and Housing Censuses. The authors measure weather extremes by the number of months in the past 36 months with temperatures or precipitation of a governorate below the 5th percentile and above the 95th percentile of the distribution of monthly temperatures or precipitation of the corresponding governorate during the period 1900–2006. Findings – This study’s results suggest that high temperatures in the origin area act as a push factor. High-temperature extremes have a positive effect on out-migration. A 1% increase in the number of months with high-temperature extremes in the original governorate results in a 0.1% increase in the number of out-migrants. Practical implications – The study suggests that people may respond to weather extremes through migration. However, climate migrants in Egypt may encounter several significant risks that authorities must address. Originality/value – This study is one of the first attempts to measure the push and pull effect of weather extremes on migration in Egypt.